THE INFLUENCE OF ISLAMIC FINANCIAL LITERACY AND INVESTMENT INTEREST ON ISLAMIC STOCK INVESTMENT DECISIONS AMONG STUDENTS - Erik Husairi; Hansen Rusliani; Firman Syah Noor (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to determine the effect of Islamic Financial Literacy (X1) and Investment Interest (X2) on Islamic Stock Investment Decisions (Y) among students of the Islamic Financial Management Study Program at UIN STS Jambi. This research employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to 62 respondents from the 2021 cohort, selected using a simple random sampling technique. Data analysis was conducted using SPSS 30, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, simultaneous F-tests, and the coefficient of determination (R²) test. The results show that, partially, Islamic Financial Literacy (X1) has a significant effect on Islamic Stock Investment Decisions, with a calculated t-value of 3.430, greater than the t-table value of 2.002, and a significance value of 0.001, less than 0.05. Investment Interest (X2) also has a significant effect on Islamic Stock Investment Decisions, with a calculated t-value of 2.997, greater than the t-table value of 2.002, and a significance value of 0.004, less than 0.05. Simultaneously, Islamic Financial Literacy and Investment Interest have a significant effect on Islamic Stock Investment Decisions, with a calculated F-value of 19.363, greater than the F-table value of 3.15, and a significance value of less than 0.001. The coefficient of determination (R²) of 0.396 indicates that the two independent variables jointly contribute 39.6% to Islamic Stock Investment Decisions, while the remaining 60.4% is influenced by other variables outside this study. It can be concluded that the higher the level of students' Islamic financial literacy and investment interest, the greater their tendency to make wise Islamic stock investment decisions in accordance with Islamic financial principles.